2004
DOI: 10.1007/s00467-004-1514-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapheresis therapy for rapidly progressive Henoch-Sch�nlein nephritis

Abstract: Six Japanese children with rapidly progressive Henoch-Schönlein purpura nephritis (HSPN) received multiple drug therapy combined with plasmapheresis (PP). After five courses of PP, multiple drug therapy, including methylprednisolone and urokinase pulse therapy, oral prednisolone, cyclophophamide, dipyridamole, and warfarin was given. At presentation, urine protein excretion and histological indices of the mean activity and chronicity were 245+/-101 mg/m(2) per hour, 6.6+/-1.2, and 1.5+/-1.3, respectively. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 8 publications
0
35
0
4
Order By: Relevance
“…There have been a number of reports on plasmapheresis (PP) for HSPN in childhood 50,51) . Hattori et al retrospectively evaluated the clinical courses of nine children with a rapidly progressive type of HSPN who were treated with plasmapheresis (PP) as the sole therapy.…”
Section: (3) Plasmapheresismentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of reports on plasmapheresis (PP) for HSPN in childhood 50,51) . Hattori et al retrospectively evaluated the clinical courses of nine children with a rapidly progressive type of HSPN who were treated with plasmapheresis (PP) as the sole therapy.…”
Section: (3) Plasmapheresismentioning
confidence: 99%
“…Two patients had normal urine, three had proteinuria of <20 mg/m 2 per hour, one had proteinuria of >20 mg/m 2 per hour, and none showed any renal insufficiency. Although this case series was examined without controls, this treatment protocol may be of benefit to children with rapidly progressive HSPN 51) . The benefits of the abovementioned treatments for treating HSPN deserve to be assessed further in larger randomized controlled trials.…”
Section: (3) Plasmapheresismentioning
confidence: 99%
“…The mechanisms by which PP benefits the patients with severe HSPN remain largely obscure. However, experimental and clinical immunologic findings suggest that the rationale for using PP in the treatment of patients with HSPN relies on the removal of IgA -containing immune complexes or aggregates, or proinflammatory mediators including cytokines and complements ; reduction in fibrinogen or other coagulation factors ; and possibly desaturation of the mononuclear phagocyte system 20,21) . In addition, the rationale for using prednisolone and MZB in case of severe HSPN is that corticosteroids and immunosuppressive agents reduce IgA production and minimize the abnormal immune response and inflammatory events that follow IgA deposition in the glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies of children with crescentic HSP nephritis have demonstrated improvement in those treated with TPE alone [77,78] and in combination with medical immunosuppression [79], although no prospective data exist. Neither HSP nor IgA nephropathy is a recommended indication for TPE at this time [3].…”
Section: Other Glomerulonephritismentioning
confidence: 99%